Fiscal effects of the Norwegian pension reform. A micro-macro assessment - Dennis Fredriksen; Erling Holmøy; Birger Strøm; Nils Martin Stølen (Statistics Norway, Research Department, 2015)
The main goal of the Norwegian pension reform of 2011 is to improve long run fiscal sustainability, not least through stronger labour supply incentives. We assess to what extent the reform is likely to live up to these intentions. To this end we combine a dynamic microsimulation model, which includes a complete description of the Norwegian population and the pension system, with CGE-modelling of the effects on all government revenues and expenditures. We find that the reform is likely to make a great fiscal impact in the long run, and higher employment plays an important role in this respect. However, the pension reform alone is far from enough to solve the Norwegians long run problem of fiscal sustainability.
Keywords: H30; H55; H62; H68; O15; 330; Pension reforms; Fiscal sustainability; Income distribution; Computable general equilibrium model; Dynamic microsimulation